Practice guidelines for BRCA1/2 tumour testing in ovarian cancer. Issue 8 (7th April 2022) - Grafodatskaya, Daria; O'Rielly, Darren D; Bedard, Karine; Butcher, Darci T; Howlett, Christopher J; Lytwyn, Alice; McCready, Elizabeth; Parboosingh, Jillian; Spriggs, Elizabeth L; Vaags, Andrea K; Stockley, Tracy L
Abstract : The purpose of this document is to provide pre-analytical, analytical and post-analytical considerations and recommendations to Canadian clinical laboratories developing, validating and offering next-generation sequencing (NGS)-based BRCA1 and BRCA2 ( BRCA1/2 ) tumour testing in ovarian cancers. This document was drafted by the members of the Canadian College of Medical Geneticists (CCMG) somatic BRCA Ad Hoc Working Group, and representatives from the Canadian Association of Pathologists. The document was circulated to the CCMG members for comment. Following incorporation of feedback, this document has been approved by the CCMG board of directors. The CCMG is a Canadian organisation responsible for certifying medical geneticists and clinical laboratory geneticists, and for establishing professional and ethical standards for clinical genetics services in Canada. The current CCMG Practice Guidelines were developed as a resource for clinical laboratories in Canada; however, they are not inclusive of all information laboratories should consider in the validation and use of NGS for BRCA1/2 tumour testing in ovarian cancers.